Disclosure experience in a convenience sample of quebec-born women living with HIV: a phenomenological study - Rouleau Geneviève; Côté José; Cara Chantal (BMC, 2012)
Abstract Background In Canada, there has been a considerable increase in the number of women infected with the human immunodeficiency virus (HIV). Within a stigmatized social context, disclosure of HIV positivity is still a prevailing concern among women. Little is known about the global understanding of how French-speaking, Quebec-born women living with HIV, live their serostatus disclosure experience. The aim of this qualitative study is to describe and understand the disclosure experience of these women. Methods We conducted semi-structured interviews with seven women. A convenience sample of French-speaking, Quebec-born women was chosen because they all responded to the criteria of wishing to share their disclosure experience. The mean age of the participants was 46 years old (SD±12). They lived with HIV for an average of 10 years; time since diagnosis varied from 8 months to 23 years. Two out of four mothers had given birth to HIV positive children. Data analysis proposed by van Manen was performed to discover the essential themes of the experience. Results Seven themes were identified to understand the experience of disclosure in women: 1) Respecting for self and confidants; 2) Feeling apprehension; 3) Exercising control to ensure protection; 4) Deliberately engaging in a process of disclosure/non-disclosure; 5) Exposing oneself to stigma and social exclusion; 6) Suffering internally; and 7) Benefitting from the positive effects of one's decision. For these women, disclosing their HIV status meant: Living the ambivalence of a paradoxical process of revealing/concealing, in a state of profound suffering, exacerbated by stigma, while also being enriched by the benefits attained. Conclusions Understanding the experience of disclosure in WLHIV is important to guide actions in the practice to support and accompany these women in their unique reality. Health professionals have to broaden their role and work on individual, interpersonal, inter-organizational and intersectoral levels. Mobilization of actors from different sectors would facilitate the implementation of pertinent and opportune interventions.